Ethiopia 1885 in Reclus’s Nouvelle Géographie Universelle - Gascon, Alain (Aethiopica, 2006)
In volume x of the Nouvelle Géographie Universelle published in 1885 Reclus dealt at length with Ethiopia. Although he never visisted Africa he wrote the first relevant geographical analysis of this region. He did not only list the descriptions and ideas prevalent at the end of the xixth century but he was the first to predict the rise of Šäwa which Mǝnilǝk was later to lead into the conquest of the Southern Highlands.